E-Commerce Produk UMKM Kecamatan Ranoyapo Menggunakan Metode Extreme Programming - Angelina Sumigar; Sondy Kumajas; Quido Kainde (JOINTER : Journal of Informatics Engineering, 2022)
Micro, small and medium enterprises (UMKM) are productive enterprises owned by individuals and business units that meet the criteria of micro enterprises. UMKM itself aims to grow and develop the ability of SMEs to become strong and independent enterprises, strengthen the role of UMKM in regional development, and create jobs and economic growth. The problem that the UMKM officials in Ranoyapo sub-discrits is facing is that there is no dedicated medium for buying and selling, making it difficult for business people to market their products widely. Based on these issues, a solution is needed to help people carry out buy and sell transactions more easily. So the author is trying to design an e-commerce website for UMKM products in Ranoyapo discrit.